Challenging content exclusivity in network industries: the case of digital broadcasting - Tom Evens (International Telecommunications Society (ITS), 2010)
Interacting with network externalities and switching costs, exclusive dealings for premium contents in digital broadcasting markets allow incumbents to deny rivals critical mass and profitable market entry. A downstream company that acquires the exclusive rights to high-quality programming in the upstream market may obtain a competitive advantage over its rivals which suffer from negative externalities. Instead of fostering competition and innovation, exclusive licensing serves as an effective entry-deterrent strategy in order to preserve market power and to leverage monopolies. Although exclusivity for premium content has long been considered the only way for guaranteeing the remuneration of the vast investments in content production and platform infrastructure, this paper challenges the profitability of this exclusivity strategy in network industries. The paper questions the traditional economic assumptions underlying exclusivity of content and argues that the increasing emergence of multi-sided platforms in the broadcasting industry creates incentives for right holders to multi-home rather than single-home their contents.
Keywords: 330; Business model; digital broadcasting; exclusivity; bundling; shared access; innovation